Práticas pedagógicas bilíngue para crianças do Instituto Cearence de Educação de Surdos - Pinheiro, Kátia Lucy (2012)
Knowing the historical evolution of deaf people education is essential to comment on what values the educational system needs to prioritize in order to educate deaf citizens, conscious of their identity and that relate to deaf culture and hearing culture with minimal difficulty. We start, therefore, from my educational experience as a deaf person and from a vision that includes the educational approaches that have supported/support deaf people education since its beginning, in order to lead the reader to understand the importance of and why offering the deaf a bilingual education. Throughout the educational process of deaf people we can see that most of the political-pedagogical programs directed to them were designed and implemented by hearing people. The participation of the deaf in the elaboration of these policies was almost nonexistent. Among some of them, we highlight Oralism, Total Communication and Bilingualism, the latter being elected by Brazilian deaf community as the most suited to their language condition. Because it has not been widely discussed and disseminated, the practice of bilingual in deaf education is still poorly understood by people, including the educational institutions specific for the deaf who claim to be bilingual. Considering this context, this work deals with the investigation of the bilingual pedagogical practices of the deaf teacher in Early Childhood classroom, at Instituto de Educação de Surdos do Ceará. This research aims to indicate the importance of bilingual pedagogical practices carried out by a deaf teacher in the educational, linguistic and cultural development of the deaf child. It is based on bibliographic studies focused on the ideas of Goldfeld, Quadros, Sklia, Moura, Sacks and Strobel, among others, and on the analysis of data collected in the field, as well as on the examination of the Pedagogical Political Project of the school. From the analysis of these instruments, we found that the classroom called Early Childhood by the institute is not characterized as such, that bilingual education is not understood by the deaf teacher nor practiced in its principles, and that the bilingual approach of education for the deaf at this school is still under implementation.